Seasonality in tourism: introducing golf as a touristic segment in order to prolong a destination’s touristic season. project of istria county in Croatia - Bohte, Lea (2015)
The present study investigates the effect seasonality has on touristic destinations and whether introducing golf tourism in the touristic offer is the right solution for dealing with this effect. This study is an in- depth single case study, supported by qualitative research. The investigation was composed of literature review which encompassed the following theoretical concepts: seasonality effect, destination life cycle, image and branding, residential and niche tourism and MICE. The qualitative research was conducted by the researcher, through the use of in- depth electronic interviews in order to show why Istria is chosen to be the best golf destination in Croatia and what benefits golf would bring to Istrian tourism. The research showed that golf, accompanied by MICE, is one of the best solutions for minimizing the seasonality effect in tourism in Istria. By introducing new segments into touristic offer, off season stay would increase, and therefore, the difference between high and off season would be decreased. Furthermore, the brand of Istria as a golf destination would become recognizable and the image of Istrian tourism would be strengthened. In addition to above mentioned conclusions, the goal of this study was to show that by changing the destination's image and focusing on niche tourism, a destination could alter its path from Decline to Rejuvenation.